Effects of age and inactivity due to prolonged bed rest on atrophy of trunk muscles - Ikezoe, Tome; Mori, Natsuko; Nakamura, Masatoshi; Ichihashi, Noriaki (European journal of applied physiology, 2012)
This study investigated the effects of age and inactivity due to being chronically bedridden on atrophy of trunk muscles. The subjects comprised 33 young women (young group) and 41 elderly women who resided in nursing homes or chronic care institutions. The elderly subjects were divided into two groups: independent elderly group who were able to perform activities of daily living involving walking independently ( n = 28) and dependent elderly group who were chronically bedridden ( n = 13). The thickness of the following six trunk muscles was measured by B-mode ultrasound: the rectus abdominis, external oblique, internal oblique, transversus abdominis, thoracic erector spinae (longissimus) and lumbar multifidus muscles. All muscles except for the transversus abdominis and lumbar multifidus muscles were significantly thinner in the independent elderly group compared with those in the young group. The thicknesses of all muscles in the dependent elderly group was significantly smaller than that in the young group, whereas there were no differences between the dependent elderly and independent elderly groups in the muscle thicknesses of the rectus abdominis and internal oblique muscles. In conclusion, our results suggest that: (1) age-related atrophy compared with young women was less in the deep antigravity trunk muscles than the superficial muscles in the independent elderly women; (2) atrophy associated with chronic bed rest was more marked in the antigravity muscles, such as the back and transversus abdominis.